Interpretação da língua brasileira de sinais a partir do gênero jornalístico televisivo: elementos verbo-visuais na produção de sentidos - Nascimento, Marcus Vinícius Batista (2011)
This research aims to conduct a descriptive analysis of the performance of LIBRAS (Brazilian Sign Language) / Portuguese translator interpreter (TILSP), in the journalism genre and in the sphere of television activity, from the work experience of the author of this research as an interpreter in this kind of discourse. For this, we chose as corpus a public domain television journalistic production, consisting of an edition cut of Programa Sentidos with the libras interpretation during it. The show is broadcasted by a cable television channel and then is available on the internet. We question which verbal-visual elements contribute and / or interfere with the libras interpretation of the journalistic genre, in the television sphere; how these elements affect the translations choices and lexical and syntactic construction in the libras interpretation from this genre, and which sense effects are produced from the interference of these elements in the process of Portuguese-LIBRAS interpretation. In this sense, The Circle of Bakhtin will serve as theoretical foundations of our research, and the comprehension of the Bakhtinian concepts of exotopy, chronotope, speech genres, enunciation, concrete utterance, text, discourse, authorship and extraverbal situation are the guidelines for the corpus analysis, which was transcribed and described from an exotopic movement shift, from the analyzed subject to the researcher, in a way that the researcher could look at himself taking into consideration the linguistic and extralinguistic elements of the target language in the act of translation/interpretation. The target language, LIBRAS, was transcribed using the Sign Language transcription system ELAN (EUDICO Language Annotator), developed by Max Planck Institute for Psycholinguistics and used on the research group Estudos da Comunidade Surda: Língua, Cultura e História (Deaf Community Studies: Language, Culture and History) in the University of São Paulo and in the course de Letras/Libras (Language Studies/Libras) of the Federal University of Santa Catarina.The analysis showed that the verbal-visual elements and images of all the reports are factors of libras linguistic marks modification, as look and body direction, and that these images are crucial for the negotiation of discursive meanings from this sphere at the time of interpretation. The incorporation of shapes and outlines of the images during signaling TILSP showed us that the whole verbal-visual component of that sphere, not only interferes with the interpretation of sign language, but also contributes to the realization of TILSP interpretive strategies aiming the transmission of senses brought by the enunciators discursive project in this genre. From the analysis we propose a theoretical and methodological possibility of referral to TILSP training and working from an enunciative-discursive perspective, adopting the analysis of Programa Sentidos as an orientation for this proposal. To this end, we used as guidelines some television journalistic productions, taking into account the possibility of future insertions of TILSP in this sphere of discourse production and realization of interpretative practices in the journalistic genre, suggesting the expansion of its operations in other genres circulating in this sphere